Antimicrobial Sensitivity among Bacterial Isolates from Sputum Samples in a Tertiary level Hospital - Kaundinnyayana, Sammodavardhana; Chaudhary, Raina; Khadka, Anjan; Bhatta, Sabita; Rayamajhi, Heleena; Sharma, Manoj (Journal of Institute of Medicine Nepal, 2024)
Introduction Emergence of antimicrobial resistance is a huge challenge in management of pneumonia especially health care associated ones. Culture and sensitivity test of the bacteria from sputum samples is not only useful for rational treatment of respiratory bacterial infections of individual cases but also for surveillance of changing sensitivity status of prevalent organisms. The aim of this study was to find the bacterial sensitivity pattern from the sputum samples and endotracheal aspirates. Methods This cross-sectional study was conducted in Shree Birendra Hospital, Kathmandu, Nepal. Standard guideline was followed for sputum culture and identification of the bacterial isolates. The antimicrobial susceptibility test was conducted using the Kirby-Bauer disc diffusion technique. Every bacterial isolate's sensitivity was studies and noted. Results The culture positivity rate was 9.87% (99/1003). Predominant isolates were gram-negative bacteria (97.4%). Pseudomonas spp. was the most frequent isolate (31%). Among the all isolates, 48.1% of Pseudomonas spp., 81.5% of Klebsiella pneumoniae, and 60% of Escherichia coli isolates showed meropenem resistance. Imipenem and meropenem resistance was observed in 91.7% of the isolates of Acinetobacter spp. Rate of resistance to carbapenems i.e. imipenem and meropenem was higher in comparison to rate of resistance to aminoglycosides in all of the gram-negative isolates. Conclusion The isolates belonging to Enterobacterales and the Acinetobacter spp. have been found to have high incidence of resistance to carbapenems in comparison to other groups of antibacterial agents.